The gap between business management curriculum and employability requirements: a case study of a selected University and bank in Cambodia. - Hum Chan (2014)
The purpose of this case study is to explore the reasons for the gap between business management curriculum at the selected university and employability requirements of bank in Cambodia. Qualitative approach with exploratory case study has been applied to examine the problem. Data were extracted through the structured interview from sixteen respondents (three curriculum designers, five employers, and eight graduate employees from banks). Seven of them were used for the pilot study in Battambang while nine others were selected for the real research in Phnom Penh. Data were classified into three categories (1) university, (2) industry and (3) graduate employees. Analytical strategy of Creswell (2007) was applied to prepare, organize, reduce, analyze and interpret data. The results of this study revealed that the gap between management curriculum and employability has existed due to four reasons (1) a loose enforcement from the government agencies on nurturing the relations between universities and industries, (2) a misperception among universities and industries toward skills development of students, (3) a scarcity of resources in implementing business management curriculum, and (4) a distancing cooperation between universities and industries in sharing information and updating the curriculum.